Crafting content: the discovery of Minecraft's invisible digital economy - Koutsouras, Panagiotis (2018)
This thesis presents an ethnographic study that aims at explicating the work of creating content in Minecraft. The existing literature paves the way in understanding Minecraft’s community by providing fragments of what players do. However, the game is studied mainly from a ludic perspective or is treated as a resource to explore distinct research agendas, instead of a field of study in itself. As such, particular phenomena that are situated inside Minecraft’s community are lost. The conducted fieldwork discovered the invisible digital economy that is part of this community. More specifically, the chapters to follow elaborate on the actors involved in this economy, covering their roles, responsibilities and goals. Furthermore, the lived work of content production is unpacked by presenting the various work practices members attend to in commissioning, creating, and delivering Minecraft content. It also becomes evident that there is a complex division of labour at play, which is based on a fragmented infrastructure as Minecraft itself does not support the wide range of activities that are necessary for carrying out the work. Essentially, actors bootstrap the market’s infrastructure by appropriating or even creating bespoke systems for conducting the various work practices that are entailed in this business. On top of that, these systems are utilised for articulation work, which is necessary for tracking progress between the geographically dispersed actors, accounting for conducted work and addressing contingent scenarios. The main contribution of this PhD project is the discovery of this digital economy, which evidently plays a significant role in Minecraft’s current form and development. Additionally, prevailing understandings of Minecraft’s ecosystem are re-visited, re-examined, and re-specified, based on the empirical evidence presented in this thesis. Finally, a number of design implications are raised with regard to addressing the game’s lack of CSCW support.